Education-related inequality in overweight and obesity among Mongolian adults. - Munkhjargal Dorjravdan; Javkhlanbayar Dorjdagva; Katsuyasu Kouda; Enkhjargal Batbaatar; Naranzul Dambaa; Tsolmon Boldoo; Bolor-Erdene Ganbold; Kumiko Ohara; Chikako Nakama; Toshimasa Nishiyama (PLOS Global Public Health)
The increasing prevalence of overweight and obesity is a serious public health problem in low- and middle-income countries, closely linked to socioeconomic status, with significant disparities observed across different socioeconomic groups. However, the association between socioeconomic status and overweight or obesity has been less studied in Mongolia. The aim of this study was to examine socioeconomic inequality in overweight and obesity among adults in Mongolia. The data for this study was derived from the Mongolian National Tuberculosis Prevalence Survey, which included 41,777 participants aged 18 years and older. We used Erreyger's concentration index to assess the degree of socioeconomic inequality in overweight and obese individuals. Socioeconomic status was measured by educational level. A decomposition analysis was applied to identify the factors contributing to inequality in overweight and obesity among Mongolian adults. Among the study population, 33.4% were overweight, and 20.7% were obese. The Erreyger's concentration index for obesity was 0.059 (p < 0.01) among men and -0.047 (p < 0.01) among women. Furthermore, obesity was concentrated among the higher-educated men and lower-educated women. The decomposition analysis results show that education, employment status, and income were the main contributors to education-related inequalities in obesity for both men and women, except the age contribution. Education-related socioeconomic inequalities in overweight and obesity exist among Mongolian adults. Future national strategies for tackling obesity should address inequalities in the root social determinants.